2014
DOI: 10.1534/g3.114.012096
|View full text |Cite
|
Sign up to set email alerts
|

Insight Into Genomic Changes Accompanying Divergence: Genetic Linkage Maps and Synteny ofLucania goodeiandL. parvaReveal a Robertsonian Fusion

Abstract: Linkage maps are important tools in evolutionary genetics and in studies of speciation. We performed a karyotyping study and constructed high-density linkage maps for two closely related killifish species, Lucania parva and L. goodei, that differ in salinity tolerance and still hybridize in their contact zone in Florida. Using SNPs from orthologous EST contigs, we compared synteny between the two species to determine how genomic architecture has shifted with divergence. Karyotyping revealed that L. goodei poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 56 publications
0
23
2
Order By: Relevance
“…Berdan et al. () demonstrated that Robertsonian fusion has played a key role in divergence and reproductive isolation between hybridizing species in another genus of fundulids ( Lucania ). Members of the F. notatus species complex similarly exhibit substantial, and potentially significant karyotypic variation.…”
Section: Discussionmentioning
confidence: 99%
“…Berdan et al. () demonstrated that Robertsonian fusion has played a key role in divergence and reproductive isolation between hybridizing species in another genus of fundulids ( Lucania ). Members of the F. notatus species complex similarly exhibit substantial, and potentially significant karyotypic variation.…”
Section: Discussionmentioning
confidence: 99%
“…homogametic (Uyeno & Miller 1971;Berdan et al, 2014). Therefore, we evaluated the 297 possibility of a male determining locus as well as a female determining locus.…”
Section: Behavioral Isolation 162mentioning
confidence: 99%
“…In both the L. parva map and the hybrid map, linkage group 1 represents a fusion of two linkage 348 groups (1A and 1B) from L. goodei. All maps had 22 additional linkage groups and are 349 numbered based on synteny (see Berdan et al, 2014) Bayesian Credible Interval 0.5-3 cM; Figure 1A). Using these same data and the L. parva map, 357…”
mentioning
confidence: 99%
See 2 more Smart Citations